The Leadership of School Principals as Drivers of Religious Moderation in Elementary Schools - Nasriadi Pakata; Kaharuddin Kaharuddin; Firman Firman (Har Press Indonesia, 2024)
Religious moderation has become a critical issue in contemporary education, particularly in multicultural societies like Indonesia. This study explores the leadership practices of school principals in promoting religious moderation in elementary schools in Rantepao Sub-district, North Toraja Regency. Employing a qualitative descriptive approach with a case study method, data were collected through observations, interviews, and documentation at two schools: SD Kristen Rantepao 5 and SD Negeri 1 Rantepao. The findings reveal that school principals play a pivotal role in fostering inclusive environments that reflect the values of tolerance, harmony, and mutual respect. Strategies include integrating religious moderation into the curriculum, implementing interfaith extracurricular activities, and adopting participatory and adaptive leadership approaches. These efforts have created harmonious school cultures, developing students’ character in appreciating diversity and strengthening relationships between schools and the surrounding community. Despite challenges, such as initial resistance from some teachers and parents, the principals successfully addressed these issues through open dialogue and persuasive approaches. The findings underscore the importance of transformational leadership in creating inclusive educational settings and promoting religious moderation to maintain harmony in diverse societies. This study contributes practical insights for developing education policies grounded in moderation and equality.